Rancang Bangun Website Desa Bulolondong Kecamatan Lamasi Timur Kabupaten Luwu - Torumpa, Nurul; Paembonan, Solmin; Apriyanto, A (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
This study aims to design, build and implement a website in Bulolondong Village, Lamasi Timur District, Luwu Regency. The research method used is the system development method with the waterfall model. Data collection techniques using data documentation methods, interviews and observations. The design of this village web in its design uses the UML (Unified Modeling Language) development method which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. Database logic design using My SQL and system interface. The software used in designing, building and implementing the system uses XAMPP as a webserver, PhpMySQL as a database. The village web design includes the home page, profile page, village information page, potential page, community service page, contact, Login page, profile management page, information management page, village potential management page, service information management page and contact management page. The information system has been tested (test case) in order to obtain an information system that runs well